Digital Transformation and its Implications for Macroeconomic Performance: A Responsive and Adaptive Management Strategy Approach - Putra, Aditya Halim Perdana Kusuma; Rivera, Kevin M. (Golden Ratio of Mapping Idea and Literature Format, 2024)
Digital transformation has become a pervasive force reshaping global business and economic landscapes. This paradigm shift goes beyond mere technological evolution, representing a fundamental reconfiguration of organizational structures, processes, and strategies. In the contemporary context, understanding and harnessing the implications of digital transformation on macroeconomic performance are crucial. This discourse explores the multifaceted impacts of digital transformation on both micro and macroeconomic dimensions, emphasizing the need for a responsive and adaptive management strategy approach.